A volunteer-supported walking programme to improve physical function in older people (the POWER Study): study protocol for a randomised controlled trial - Grede, Nina; Rieckert, Anja; Muth, Julia; Steinbuck, Joana; Weissbach, Sabine; Schneider, Annika; Weber-Schicker, Beate; Freiberger, Ellen; Jegan, Nikita; Donner-Banzhoff, Norbert; Sönnichsen, Andreas (BMC Geriatrics, 2021)
Background: Currently 21% of the German population is older than 65 years. Above this age, the risk of suffering from chronic disease and mental disorders increases rapidly. Therefore, physical inactivity is one of the most important public health concerns among older people. To address this issue, we have conceptualised and evaluated a simple and low-threshold intervention, which requires only minimal demand on the participants, targeting older people with inadequate activity levels. The aim of the POWER Study is to investigate whether volunteer-supported outdoor-walking improves physical function and quality of life in older people. Methods/design: In a randomised, controlled interventional superiority-trial, individuals older than 65 years of age living in the community or nursing homes will be randomised into two groups. The study will be conducted in two study centres with assessments at baseline, 6 and 12 months. The intervention group will participate in a supported physical activity intervention for 6 months. An assigned volunteer will visit them three times a week for an outdoor walk between 30 and 50 min, or equivalent indoor activity. Persons in the control group will be invited to two lectures covering topics related to health. Primary endpoint is the physical function measured by the Short Physical Performance Battery (SPPB) at baseline, after 6 and 12 months. Secondary and safety endpoints will be quality of life (EQ. 5D), fear of falling (Falls Efficacy Scale), physical activity (activity diary), cognitive executive function (clock drawing test), falls requiring medical attention, hospitalisation and death. Primary analysis will be carried out by intention to treat. Discussion: We expect the intervention to improve the overall health status of the participants in a wide range of health-related outcomes. If effectiveness can be shown, the intervention will close an important gap in current services for older people. We will disseminate our experiences and results in the form of informational documents (training manual) to allow municipalities and health care organisations to implement a similar intervention. Trial registration: The trial was registered on 31 Aug 2018; German Clinical Trials Register (www.germanctr.de), Deutsches Register Klinischer Studien: DRKS00015188.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Exercise; Healthy ageing; Older people; Peer-support; Physical activity; Quality of life; Walking